Communicating Science to the Public – Synergy between Academia and Media (Journal of Science, Technology and Innovation Policy, 2021)
It is considered inadequate to rely solely on our education system to provide citizens with the knowledge they require in order to effectively navigate within this modern, highly technical society, and make well-informed policy choices. Due to the explosive increase of new knowledge, no one person has the capacity to “know it all”. In order to bring accurate, relevant information, from the front line of research, to the pages of newspapers, academics and the general public must be willing and able to communicate among each other. However, according to the author, effective communication does not always come easily. Academics complain that the general public does not comprehend some of the basics of their methods, including peer reviews, the incremental nature of research, and the proper interpretation of statistics. Conversely, members of the general public complain that academics becomes unnecessarily wrapped up in the jargon on such matters, and thus fail to explain their work in a simple and cogent manner. The consequence of this apparent impasse is that important knowledge may go begging for lack of communication. Although major newspapers cover research successfully, the majority often lack the wherewithal to devote precious resources to scientific stories, which are generally difficult to write, and may not attract a wide audience. The writing, and in turn the communication, of these stories, requires a high level of mutual trust between academics, who reflect the object of the story, and the readers who read it.
Keywords: Communicating science; academia and media